2017
DOI: 10.3945/ajcn.116.144972
|View full text |Cite
|
Sign up to set email alerts
|

Tea catechin and caffeine activate brown adipose tissue and increase cold-induced thermogenic capacity in humans

Abstract: The thermogenic effects of green tea catechin have been repeatedly reported, but their mechanisms are poorly understood. The aim of this study was to investigate the acute and chronic effects of catechin on brown adipose tissue (BAT), a site specialized for nonshivering thermogenesis, in humans. Fifteen healthy male volunteers underwent fluorodeoxyglucose-positron emission tomography to assess BAT activity. To examine the acute catechin effect, whole-body energy expenditure (EE) after a single oral ingestion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 43 publications
5
78
0
4
Order By: Relevance
“…Consistent with our data, other studies have shown that many plant extracts rich in catechins and methylxanthines, like guarana, may activate AMPK concomitantly with reducing weight (Henning et al, ) and increase energy expenditure (Yoneshiro et al, ). Interestingly, when administered together, catechin and caffeine increase energy expenditure in subjects with metabolically active BAT but not in subjects with negligible activity (Yoneshiro et al, ), suggesting that the anti‐obesity effect of catechin and caffeine occurs via BAT activation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our data, other studies have shown that many plant extracts rich in catechins and methylxanthines, like guarana, may activate AMPK concomitantly with reducing weight (Henning et al, ) and increase energy expenditure (Yoneshiro et al, ). Interestingly, when administered together, catechin and caffeine increase energy expenditure in subjects with metabolically active BAT but not in subjects with negligible activity (Yoneshiro et al, ), suggesting that the anti‐obesity effect of catechin and caffeine occurs via BAT activation.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, guarana activated BAT by promoting mass increase, mitochondrial biogenesis, and UCP1 overexpression, which are important mechanisms of BAT activation (Lidell et al, ; Sanchez‐Delgado et al, ). Corroborating our data, many other extracts/compounds effective in weight management have been shown to activate BAT in humans and animal models (Saito & Yoneshiro, ; Yoneshiro et al, ; Yuan et al, ). BAT activation can be stimulated by other factor like ambient temperature, which is a crucial factor in determining organismal energy balance, at least in part through BAT activation (Lidell et al, ; Sanchez‐Delgado et al, ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The caffeine in white tea may, in part, be responsible for this result, as it is thermogenic and stimulates the oxidation of fat (for review, see Harpaz et al ., ). However, caffeine is unlikely to be solely responsible for this finding, as catechins containing caffeine have a greater thermogenic effect than caffeine alone (Heber et al ., ; Yoneshiro et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The caffeine in white tea may, in part, be responsible for this result, as it is thermogenic and stimulates the oxidation of fat (for review, see Harpaz et al, 2017). However, caffeine is unlikely to be solely responsible for this finding, as catechins containing caffeine have a greater thermogenic effect than caffeine alone (Heber et al, 2014;Yoneshiro et al, 2017). Values in the same column followed by the same lower-case letters (analysed by unpaired t-test) and values on the same line followed by the same capital letters (analysed by one-way repeated measures ANOVA) are not significantly different (P > 0.05).…”
Section: Discussionmentioning
confidence: 99%